2022
DOI: 10.1073/pnas.2119854119
|View full text |Cite
|
Sign up to set email alerts
|

USP13 promotes deubiquitination of ZHX2 and tumorigenesis in kidney cancer

Abstract: Clear cell renal cell carcinoma (ccRCC) is characterized by the loss of tumor suppressor Von Hippel Lindau (VHL) function. VHL is the component of an E3 ligase complex that promotes the ubiquitination and degradation of hypoxia inducible factor α (HIF-α) (including HIF1α and HIF2α) and Zinc Fingers And Homeoboxes 2 (ZHX2). Our recent research showed that ZHX2 contributed to ccRCC tumorigenesis in a HIF-independent manner. However, it is still unknown whether ZHX2 could be modified through deubiquitination even… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 46 publications
1
21
0
Order By: Relevance
“…Consistent with findings in HCC, low ZHX2 expression correlates with poor prognosis of thyroid cancer (7), multiple myeloma (8)(9)(10), and chronic lymphocytic leukemia (11,12). On the contrary, ZHX2 promotes the development of ccRCC (13)(14)(15), TNBC (16), and gastric cancer (17,18). Beyond regulating cancer development, the latest reports have shown that ZHX2 involves in several other physiological or pathological processes, including cell differentiation and development (19)(20)(21), lipid metabolism (22)(23)(24), and viral replication (25,26).…”
Section: Introductionsupporting
confidence: 75%
See 1 more Smart Citation
“…Consistent with findings in HCC, low ZHX2 expression correlates with poor prognosis of thyroid cancer (7), multiple myeloma (8)(9)(10), and chronic lymphocytic leukemia (11,12). On the contrary, ZHX2 promotes the development of ccRCC (13)(14)(15), TNBC (16), and gastric cancer (17,18). Beyond regulating cancer development, the latest reports have shown that ZHX2 involves in several other physiological or pathological processes, including cell differentiation and development (19)(20)(21), lipid metabolism (22)(23)(24), and viral replication (25,26).…”
Section: Introductionsupporting
confidence: 75%
“…ZHX2 protein hydroxylation at proline 427, 440, and 464 allows VHL to bind and promote its protein degradation (13). However, a deubiquitinase USP13 inhibits the ubiquitination of ZHX2 and enhances its stability (15). A recent study found that the N-terminal methylation (Na-methylation) of ZHX2 by the methyltransferase NRMT1 regulates its transcription factor activity and its occupancy on targeted promoters (50).…”
Section: Control Of Zhx2 Expressionmentioning
confidence: 99%
“…For instance, USP13 was shown to be upregulated in lung cancer and ovarian cancer, and its intracellular level was associated with the progression of malignant tumors. [ 18a,41 ] In addition, USP13 was also found to be involved in renal cell carcinoma, [ 19 ] which indicated the potential relevance between USP13 and kidney disease. However, the role of USP13 in other kidney diseases is still obscure.…”
Section: Discussionmentioning
confidence: 99%
“…Xie et al discovered that USP13 was essential for the progression of clear cell renal cell carcinoma, and this effect was mediated by the regulation of ZHX2. [19] In addition, little is known about the relevance between USP13 and other kidney diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, ccRCC is triggered by the biallelic inactivation of the tumor suppressor gene Von Hippel-Lindau ( VHL ) in renal epithelial cells, which deregulates the hypoxia-inducible factors ( HIFs ), including HIF-1a and HIF-2α [ 10 , 11 ]. VHL can form a classical E3 ubiquitin ligase complex with elonginB, elonginC, Cullin2, and Rbx1 [ 12 ].…”
Section: Introductionmentioning
confidence: 99%